Learning Japanese "Kaiwa" Based on Strategy - Ferdy Dj. Rorong; Diane M. Tengker (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
This study regarding the learning Japanese “Kaiwa” based on strategy. The result shows that strategies are grouped into direct strategies and indirect strategies. By using strategies that are in accordance with the wishes and character of the learner, maximum results can be achieved in learning any language. In Quantum Teaching it is said that humans teach 10% of what is read, 20% of what is heard, 30% of what is seen, 50% of what is seen and heard 70% of what is said and 90% of what is said and done because education will be effective when we accept the theory and be accompanied by exercises. One thing that should be underlined is the natural situation in practice, there is a tendency to have a significant influence in the process of achieving language learning.